2012
DOI: 10.1016/j.juro.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Statin Therapy is not Associated with Biochemical Recurrence After Radical Prostatectomy: Our Experience and Meta-Analysis

Abstract: Our findings are consistent with the results of the meta-analysis, which indicated that preoperative statin use does not impact the overall risk of biochemical recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…17 Furthermore, our study and three other studies on the effect of statins on the outcome of PC after RP did not show a lower PSA in patients taking statins at the time of surgery. 11,13,14 In contrast to the results of our and other previous studies, Hamilton et al 17 found statin use to be associated with decreased risk of BCR after RP after adjustment for clinical and pathological features. Adding Gleason-Score to their multivariable model generated the largest shift in HR for statin use.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…17 Furthermore, our study and three other studies on the effect of statins on the outcome of PC after RP did not show a lower PSA in patients taking statins at the time of surgery. 11,13,14 In contrast to the results of our and other previous studies, Hamilton et al 17 found statin use to be associated with decreased risk of BCR after RP after adjustment for clinical and pathological features. Adding Gleason-Score to their multivariable model generated the largest shift in HR for statin use.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation is in line with five previously published studies [11][12][13][14][15] and a recent meta-analysis, 19 which could not reveal a significant association of statin use with BCR after RP. In contrast, Ritch et al detected an increased risk of BCR in PC patients using statins after RP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding prostate cancer outcomes after treatment, three meta-analyses have reported a null association between statin use and risk of recurrence (Mass, et al 2012; Park, et al 2013; Scosyrev, et al 2013). However, the studies contributing to these meta-analyses were few and most examined statin use at the time of prostate cancer treatment.…”
Section: Obesity and Related Co-morbidities As Modifiable Lifestylmentioning
confidence: 99%